Electronic structures of peanut-shaped fullerene tubes - Hiroyuki Nakayama, Tomoya Ono, Hidekazu Goto and Kikuji Hirose (Science and Technology of Advanced Materials, 2007)
We have investigated electronic structures of the peanut-shaped polymerized fullerene with so-called P55, P56 and P66 tubular linkage structures. The stable atomic configurations in these one-dimensional or two-dimensionally bundled tubes are searched out by a tight-binding calculation, and then their electronic structures are evaluated by using an ab initio density functional calculation. The electronic structures change drastically depending on the bonding interaction between the tubes. The P66 tube can show metallic conduction when it is bundled two-dimensionally.